2008
DOI: 10.1111/j.1365-2524.2008.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

TheMental Capacity Act 2005: promoting the citizenship of people with dementia?

Abstract: The Mental Capacity Act 2005 came into force in England and Wales during 2007. The Act enshrines a legal right to autonomy (negative and positive) of people lacking decision-making capacity, such as people with dementia. This paper examines the extent to which the legislation promotes the social citizenship of people with dementia, focusing on its effectiveness in protecting liberty and promoting self-determination and in providing social rights to facilitate autonomy. In particular, the author considers the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 18 publications
0
89
0
Order By: Relevance
“…Particularly in nursing literature, focus has been placed on the care recipient's role in care planning and decision making in residential, hospital, or community settings 1,2 . This discussion has been extended to people with dementia, centring on notions of personhood, citizenship, and the importance of autonomy and choice 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in nursing literature, focus has been placed on the care recipient's role in care planning and decision making in residential, hospital, or community settings 1,2 . This discussion has been extended to people with dementia, centring on notions of personhood, citizenship, and the importance of autonomy and choice 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The MCA proposed that individuals lacking mental capacity should be enabled to exercise their extant (or remaining) decision-making capacity (5). This legal definition does not give specific measures of an individual's ability to comprehend information.…”
Section: Definition Of Capacitymentioning
confidence: 99%
“…Prior to this law, family members and professionals often made decisions on behalf of people with dementia without regard for their capacity, thereby depriving them of decisional autonomy (Collopy 1995, Boyle 2008. Indeed, previous research into decision-making in dementia only examined the views of family members (Hicks andLam 1999, Adams 2006).…”
Section: The Agency Of Women With Dementia and Everyday Decision-makingmentioning
confidence: 99%
“…In addition, women with dementia who could still cook were constrained by their husbands from using their extant decisional and executional capacity (see Collopy 1995). Yet, it should be noted that 'assisted autonomy' is necessary to promote the agency of people with dementia (Boyle 2008). Although Sabat (2003, p. 85) had suggested that people with dementia are susceptible to 'malignant positioning' by others which can undermine their sense of social competency, it is important to note that, at times, this negative positioning may be explained more by gender inequality than by -what Ward et al (2008) referred to as -'cognitive disablism'.…”
Section: Competency and Capacitymentioning
confidence: 99%